Moisture diffusivity and energy consumption in palm oil fruit drying - พระเมือง, สุรจิตร์ (KKU Science Journal, 2017)
Drying of palm oil fruits in laboratory were performed at temperatures of 60, 70, 80, 90 and 100 oC for 8 hours with initial moisture contents decreasing from 46.25%, 36.73%, 41.06%, 45.94%, and 42.50% dry basis to 20.08%, 14.51%, 13.30%, 10.35% and 8.59% dry basis respectively. At 100 oC moisture content and drying were lowest suitable for crude palm oil extraction. The moisture ratios of the higher temperature decreased rapidly than the lower ones. Moisture diffusivity coefficients for palm fruits drying were ranged between (1.04 – 1.82) × 10-9 m2/s depending on drying temperature. Specific moisture extraction rate and specific energy consumption were ranged of (5.04 – 7.97) × 10-4 kg/kJ and 12,542.66 – 19,825.53 kJ/kg, respectively. The drying of palm fruits at 90 oC consumed minimum energy.